A study of the evaluation of advertising message effectiveness with particular reference to the life assurance industry in South Africa - Wigram, Nigel Francis (Marketing, 2024)
[ page 3-5, 3-8, A7-11, 2 missing] This thesis presents a method of gauging advertising effectiveness through the measurement of changes in purchasing patterns caused by the controlled exposure to advertisements. The concept is not entirely new, but it is thought that this is the first time that a practical system has been designed and tested. Certainly it is new to the insurance industry in South Africa. In order to provide a framework within which to measure advertising effectiveness, the thesis proposes certain models of the way in which advertising works for the insurance industry. Although these models provide the basis for the empirical studies, they are not essential to the proposed methodology. Advertising effectiveness can, however, only be measured against agreed objectives and implies a defined scale of values. Those objectives and, values must in their turn be absolutely relevant to the true purpose of the advertisement. It is suggested that in certain other measurement systems relevance is forced to yield to expediency. Essentially the method requires that advertising messages are dispatched by direct mail to random samples drawn from a list which effectively represents the total universe of the target market.